Hero turned villain: NLRP3 inflammasome-induced inflammation during influenza A virus infection. Issue 4 (5th October 2016) - Ong, James D H; Mansell, Ashley; Tate, Michelle D
Abstract : Review on the role of NLRP3 inflammasomes during IAV infection. Abstract: The severity of influenza A virus (IAV) infection can range from asymptotic to mild to severe. Infections, such as those seen following outbreaks of avian IAV, are associated with hyperinflammatory responses and the development of fatal disease. There is a continual threat that a novel or pandemic IAV will circulate in humans with high rates of mortality. The neuronal apoptosis inhibitor protein, class 2 transcription activator of the MHC, heterokaryon incompatibility, telomerase-associated protein 1, leucine-rich repeat, and pyrin domain-containing protein 3 (NLRP3) inflammasome is an innate immune sensor that has been shown to be critical for the secretion of the potent proinflammatory cytokines, IL-1β and IL-18, as well as chemokine production and cellular inflammation in vivo following IAV infection. Initial studies illustrated a protective role of NLRP3 during severe IAV infection in mice. However, the NLRP3 inflammasome may be a hero that turns villain in the later stages of severe IAV infection via the promotion of a hyperinflammatory state. Current treatments for patients who present to hospitals with a severe IAV infection are limited. The understanding of the mechanisms involved in the induction of NLRP3-dependent inflammation during severe IAV infections may provide new therapeutic targets that reduce human mortality.